(untitled) (International Journal of Engineering and Computer Science, 2017)
In the contemporary era, Data is the most valuable resource that is used in day to day life from an individual to large organizations. Database contains useful and confidential information so it becomes necessary to protect it from any unauthorized access. Any unauthorized user can try to perform unauthorized activities at unauthorized time on sensitive data. So to prevent the database from any misuse, different security mechanisms are applied to the database to make it secure. This paper focuses on the challenges and security mechanisms in database.